Implementation of School Literacy Activities to Build Reading Habits for Grade III Elementary School Students - Rahayu, Arifah; Widodo, Susilo Tri (Elementary School Teacher, 2021)
This study aims to describe school literacy activities to develop reading habits for third grade students of SD NegeriDiponegoro. This study used descriptive qualitative method. The methods of data collection using interviews,documentation, and field notes. Then the data is tested using credibility and confirmability tests. The results of this studyindicate that: (1) school literacy activities at the habituation stage are proven by providing facilities and infrastructure tosupport, creating an environment which is rich of text, the role of teachers and implementing 15 minutes of readingactivities regularly and can repeatedly build students' reading habits. (2) The supporting factors of school literacyactivities are facilities and infrastructure, allocation of funds and time, also the role of teachers. a, the inhibiting factorsare the students low reading interest, incomplete facilities and infrastructure, also the teachers are not optimal in schoolliteracy activities. (3) The roles of teacher in school literacy activities are to direct activities and help students in choosinga book. (4) The ways to build students' reading habits through school literacy activities, they are providing various typesof books which are students like, increasing students' interest in reading books, motivating students' and forming anenvironment that supports reading habits. The conclusion of this study is that school literacy activities can build students'reading habits through 15 minutes of reading regularly and repeatedly supported by facilities and infrastructure, theenvironment and the role of the teacher.Keywords: school literacy activities; reading habit